ANALISIS INOVASI DAN KUALITAS PRODUK DALAM MENINGKATKAN KEPUTUSAN PEMBELIAN KONSUMEN KOTA MEDAN - Daniel Valentino Lay; Hommy Dorthy Ellyany Sinaga; Rahmad Dianta Purba (Jurnal Riset Multidisiplin Edukasi, 2026)
This study examines the role of innovation and product quality in enhancing consumer purchase decisions in Medan using a descriptive qualitative approach. Case studies were conducted across representative product categories in the local market. Data were collected through in depth interviews, participant observation at points of sale and after sales services, and documentation of product materials and customer testimonials. Thematic analysis involving data reduction, categorization, and source triangulation revealed that functionally relevant innovation and consistent product quality are primary drivers of perceived value, accelerate decision making, and foster customer loyalty. The study also identifies several problems related to the variables of innovation, product quality, and the purchase decision process that manufacturers and retailers must address.